PEMBERDAYAAN DIGITAL DENGAN PELATIHAN LITERASI DASAR, KETERAMPILAN DAN WIRAUSAHA DIGITAL BAGI PENGURUS PONDOK YATIM & DHU’AFA TANJUNG BARAT - Fitrian, Andry; Mayanty, Sri; Karlina, Elin; Safitri, Hania Irba; Kurniawati, Laila Dwi Putri (Jurnal Abdi Insani, 2025)
The development of digital technology has opened significant opportunities to enhance human resource capacity, including in social institutions such as orphanages and foundations for the underprivileged. However, limitations in digital literacy, digital skills, and digital entrepreneurship often become obstacles in optimizing the use of technology. This community service program aims to empower the administrators of Pondok Yatim and Dhu’afa Tanjung Barat through training in basic digital literacy, digital skills, and digital entrepreneurship. The method applied was participatory training, carried out in three stages: preparation, implementation, and evaluation. The results of the program lead to several conclusions: first, the implementation of digital empowerment through training in literacy, skills, and digital entrepreneurship was successfully conducted for the administrators of Pondok Yatim & Dhu’afa Tanjung Barat; second, based on program evaluation, the average N-Gain Score was 0.796 or 79.64%, categorized as high, indicating that participants’ competencies increased optimally after the training. Furthermore, a satisfaction survey of the participants showed an average score of 96%, reflecting that this digital empowerment program was highly satisfying and met their expectations. Thus, the training program not only contributes to individual capacity-building but also supports the sustainability of the institution in the era of digital transformation.